Examining trends in multiple parameters of seasonally‐relative extreme temperature and dew point events across North America. (9th October 2020) - Lee, Cameron C.; Obarein, Omon; Sheridan, Scott C.; Smith, Erik T.; Adams, Ryan
Abstract: Concurrent with the background rise in global mean temperatures, changes in extreme events are also becoming evident, and are arguably more impactful on society. This research examines trends in three components of seasonally‐relative extreme temperature and humidity events in North America that directly influence human thermal comfort: event frequency, duration, and areal extent. Results indicate that for the majority of the study domain, changes in these events are in the expected direction with changes in means. Extreme heat events are generally increasing throughout the domain, with the largest changes in summer and autumn in the eastern portion of Canada and the United States. Cold events are largely decreasing in these same locations and seasons, with additional widespread decreases in winter. Interestingly, significant increases in cold events are also evident in autumn in parts of the western United States. Extreme humidity events are showing an even greater change than temperature events – nearly all of Canada and most of the United States is seeing significant increases in extreme humid events and decreases in dry events, while the southwestern deserts show widespread significant increases in dry events, especially in winter and spring. Changes in event duration and spatial extent mimic these results. Importantly, this research demonstrates that there are regions that show changes to extreme events that differ from the overall changes in means, highlighting the importance of looking beyond climate averages to examine not only extreme events, but changes in higher‐order statistical moments. Abstract : This research examines trends in three components of seasonally‐relative extreme temperature and humidity events in North America: frequency, persistence, and areal extent. While many changes in these events are in the expected direction, opposite extremes are not changing with the same magnitude, and trends vary markedly by season. Most importantly, some regions show changes to extreme events that differ from the overall changes in means, highlighting the importance of examining not only extreme events, but changes in higher‐order statistical moments.